Good Manufacturing Practice (GMP) Compliance for Phage Therapy Medicinal Products - Bretaudeau, Laurent; Tremblais, Karine; Aubrit, Françoise; Meichenin, Marc; Arnaud, Isabelle (Frontiers in Microbiology, 2020)
Facing the emergence of difficult-to-treat bacterial infections, the perspective of using bacteriophages has re-gained interest in many countries. In terms of pharmaceutical classification in EU and USA, phages are considered as anti-infectious medicinal products and biological products, given the intended use and their live nature. During the production steps, the compliance with the Good Manufacturing Practice (GMP) represents the gold-standard to ensure the quality, safety and efficacy of medicinal products, either investigational or approved. In practice, the implementation of GMP rules for phage therapy medicinal products benefits from the long history of vaccine development. Accordingly, a well-structured strategy can be defined for each medicinal product, taking into account the specified indication (i.e. the target bacteria species, the infected site, the route of administration, the product composition). Based on the experience of different phage therapy medicinal products from the recent years, the most important requirements to achieve and claim GMP grade are reviewed here, including for genetically-modified phages. Like all new medicinal products, the manufacturing of investigational phages incorporates significant challenges. However, the use of GMP-certified phages provides the best guarantee for the rigorous assessment of quality, safety and efficacy during the clinical development of phage medicinal products, thus appears as a key component for the successful development of phage therapy approaches.